2019
DOI: 10.25259/sni-123-2019
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Kyphoplasty, Vertebroplasty, or Non-Surgical Treatment of Traumatic/Atraumatic Osteoporotic Vertebral Compression Fractures: A Short Review

Abstract: Background:Although the majority of patients with traumatic/atraumatic osteoporotic vertebral compression fractures (OVCFs) may be managed with non-surgical treatment (NST), a subset (e.g. 40%) with significant pain, loss of vertebral height, and other factors may warrant percutaneous vertebroplasty (V), or percutaneous kyphoplasty (K).Methods:We compared the impact of these three treatment modalities, V, K, or NST, for managing OVCFs.Results:In several studies, both V and K resulted in comparable improvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…Conservative treatment includes oral medications such as analgesics, gabapentinoids, hormone therapy with calcitonin, bisphosphonates, physical modalities, and bracing. Although the majority of VF may be managed with conservative non-surgical treatment, a subset of these with significant vertebral height loss, mechanical disruption, and uncontrollable pain (around 40%) may warrant minimally invasive vertebral augmentation (VA) (Figure 5) [92]. Despite the initial higher costs associated with interventional pain management, the overall expenditure associated with conservative care over a 4-year span and VA is similar [93].…”
Section: Vertebral Fracturesmentioning
confidence: 99%
“…Conservative treatment includes oral medications such as analgesics, gabapentinoids, hormone therapy with calcitonin, bisphosphonates, physical modalities, and bracing. Although the majority of VF may be managed with conservative non-surgical treatment, a subset of these with significant vertebral height loss, mechanical disruption, and uncontrollable pain (around 40%) may warrant minimally invasive vertebral augmentation (VA) (Figure 5) [92]. Despite the initial higher costs associated with interventional pain management, the overall expenditure associated with conservative care over a 4-year span and VA is similar [93].…”
Section: Vertebral Fracturesmentioning
confidence: 99%
“…Percutaneous vertebral augmentation procedures such as PVP and PKP has long been used to treat acute pain resulting from VCF [2,13,14]. PVP involve the percutaneous injection of bone cement into a fractured vertebra, with the intent of stabilizing the vertebral body, whereas PKP involves the inflation of a small balloon to create a cavity within the vertebra, which subsequently is filled with bone cement [15].…”
Section: Surgical Management Of Osteoporotic Vcfmentioning
confidence: 99%
“…Uncontrolled trials of PVP and PKP have shown the procedures can provide better pain relief, higher quality of life, and postoperative restoration of vertebral body height when compared with conservative management [14]. However, in 2009, two double-blind RCTs of PVP for painful osteoporotic VCFs were published [19,20].…”
Section: Surgical Management Of Osteoporotic Vcfmentioning
confidence: 99%
“…The materials undergo in situ polymerization following injection into the vertebral body and harden to provide adequate mechanical support to the vertebral column [ 4 ]. Currently, the most popular are polymethylmethacrylate (PMMA)-based acrylic bone cements with high mechanical strength and successful use in VP or KP to provide pain relief and stability to the fracture site [ 1 , 2 , 3 ]. However, PMMA presents some potential drawbacks, including non-biodegradability, monomer toxicity, heat generation during exothermic polymerization (up to 60 °C), and higher stiffness than that of cancellous bone, all of which possibly contribute to fractures of adjacent vertebrae after VP [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bone cements are widely used in different applications of orthopedic surgery due to their injectability, especially for minimally invasive surgical techniques, such as vertebro-Materials 2021, 14, 3873. https://doi.org/10.3390/ma14143873 https://www.mdpi.com/journal/materials plasty (VP) or kyphoplasty (KP; [1][2][3]). They are generally supplied as self-curing systems, consisting of separate powder and liquid phases, and mixed prior to use during surgery.…”
Section: Introductionmentioning
confidence: 99%